2013
DOI: 10.9734/bjpr/2013/4003
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Hepatoprotective Potential of Tinospora cordifolia, Tinospora sinensis and Neem-guduchi

Abstract: Aims: Aim of this study was to evaluate the comparative efficacy of Tinospora cordifolia (Willd.) Miers ex Hook. F., Tinospora sinensis (Lour.) Merrill and T. cordifolia growing on Neem (Azadirachta indica A. Juss.) called Neem-guduchi. Study Design: Selected species have been widely used in the traditional medicine systems in various dosage forms to treat liver disorders. They are of common occurrence and are being used as substitutes to each other. There is no comparative hepatoprotection study yet published… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…It is locally known as gulancha and is a lofty, woody, entirely glabrous climber (Yusuf, Chowdhury, Wahab, & Begum, 1994). Previous research has shown that the methanol extract of the plant has significant antioxidant properties (Ahmad et al, 2016), while other species of the Menispermaceae such as Tinospora cordifolia and Tinospora sinensis have also been shown to possess significant hepatoprotective activities (Bishayi, Roychowdhury, Ghosh, & Sengupta, 2002;Nagarkar et al, 2013). Various phytochemicals, including alkaloids, lignans, triterpenes, nucleosides, and sterols, are known to be present in the plant (Ahmad, Jantan, & Bukhari, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is locally known as gulancha and is a lofty, woody, entirely glabrous climber (Yusuf, Chowdhury, Wahab, & Begum, 1994). Previous research has shown that the methanol extract of the plant has significant antioxidant properties (Ahmad et al, 2016), while other species of the Menispermaceae such as Tinospora cordifolia and Tinospora sinensis have also been shown to possess significant hepatoprotective activities (Bishayi, Roychowdhury, Ghosh, & Sengupta, 2002;Nagarkar et al, 2013). Various phytochemicals, including alkaloids, lignans, triterpenes, nucleosides, and sterols, are known to be present in the plant (Ahmad, Jantan, & Bukhari, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Various phytochemicals, including alkaloids, lignans, triterpenes, nucleosides, and sterols, are known to be present in the plant (Ahmad, Jantan, & Bukhari, 2016). Previous research has shown that the methanol extract of the plant has significant antioxidant properties (Ahmad et al, 2016), while other species of the Menispermaceae such as Tinospora cordifolia and Tinospora sinensis have also been shown to possess significant hepatoprotective activities (Bishayi, Roychowdhury, Ghosh, & Sengupta, 2002;Nagarkar et al, 2013). Conversely, other workers have suggested that the stem juice of T. crispa possesses significant hepatotoxicity (Huang, Tu, Wang, & Huang, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…F. & Thoms is an important medicinal climber, found in tropical regions of India, China, Sri Lanka, and Bangladesh (Mittal et al 2014). Besides, it is rich with a variety of natural chemical constituent’s viz., tinosporin, cordifolioside, magnoflorine, palmetine, isocolumbin, tinocordiside, glycoside, cordifolioside syringing (Nagarkar et al 2013; Choudhry et al 2014) and cures a number of ailments such as viral infections, cancer, diabetes, inflammation, neurological disorders, psychiatric problems, microbial infection, hyper tension and HIV aids (Jayaganthan et al 2013; Nagarkar et al 2013; Joladarash et al 2014; Mittal et al 2014). Recently, this plant species is extensively using to cure chikungunya and dengue.…”
Section: Introductionmentioning
confidence: 99%
“…10 Literature depicting the safety of T. cordifolia shows it to be safe. 11 12 13 In published literature, Satwa made from the stems of T. sinensis has been shown to possess hepatoprotective activity against paracetamol 10 14 and alcohol-induced 15 hepatotoxicity. Moreover, the ethanolic extract of T. sinensis root has been reported to exhibit hepatoprotective activity in carbon tetrachloride-induced hepatotoxicity in rats.…”
Section: Introductionmentioning
confidence: 99%